2021
DOI: 10.3390/polym13020291
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Hydrophobically Modified Xylans

Abstract: Xylan is a major type of hemicellulose that has attracted a lot of research and development activities. It is often derivatized in order to improve its properties. In the literature, hydrophobic modification of polymers is often used to produce surfactant-like materials and associative thickeners. In this work, we have derivatized xylan with alkyl ketene dimer (AKD) and two types of alkenyl succinic anhydrides (ASAs). The xylan-AKD derivatives have been made at 90 °C, using dimethyl sulfoxide as solvent and 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…It was observed that the grafting of the octenyl succinate chains onto the SPG may have caused the lower degradation temperatures, which is illustrated by the fact that the introduction of the OS group negatively affected the thermal stability of SPG. The decrease in the thermal stability was caused by the weakened hydrogen bonds between the hydrophobic alkenyl group and SPG, resulting in a lower required energy input for bond breakage, which is similar to Cheng’s report [ 40 ]. The decrease in the thermal stability was caused by the weakened hydrogen bonds between the hydrophobic alkenyl group and SPG, resulting in a lower required energy input for bond breakage [ 41 ].…”
Section: Resultssupporting
confidence: 86%
“…It was observed that the grafting of the octenyl succinate chains onto the SPG may have caused the lower degradation temperatures, which is illustrated by the fact that the introduction of the OS group negatively affected the thermal stability of SPG. The decrease in the thermal stability was caused by the weakened hydrogen bonds between the hydrophobic alkenyl group and SPG, resulting in a lower required energy input for bond breakage, which is similar to Cheng’s report [ 40 ]. The decrease in the thermal stability was caused by the weakened hydrogen bonds between the hydrophobic alkenyl group and SPG, resulting in a lower required energy input for bond breakage [ 41 ].…”
Section: Resultssupporting
confidence: 86%
“…An alkylketene dimer and an alkenyl succinic anhydride were used to hydrophobize xylan in a recent study, but thermoplasticity was not achieved (Cheng et al, 2021). Previous studies have demonstrated that ring opening polymerization of ε-caprolactone on hemicellulose can make it melt processable (Farhat et al, 2018;Svärd et al, 2018) We previously demonstrated that AX with a high araf/xylp (0.8 and 1.1) after one-step and two-step functionalization with BuGE can potentially be processed using the polymer processing technique (Börjesson et al, 2019a(Börjesson et al, , 2019bDeralia et al, 2021aDeralia et al, , 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…However, free hydroxyl groups are available for chemical functionalization of xylan (i.e., esterification, etherification, crosslinking, etc.) with hydrophobic functional groups, especially when it is used for packaging and coating applications [18].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical reaction of AKD with xylan hemicelluloses occurs at free hydroxyl groups from 2 and/or 3 positions of xylan monomer unit. As result, the hydrophobic moieties of β-ketoester and fatty acid chains are introduced, and the amphiphilicity as well as the surface activity of hemicellulose are enhanced (Figure 1) [18,45]. in the field of new types of hydrophobic xylans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation